16. Presynaptic and postsynaptic inhibition in the human dorsal column nuclei. Issue 12 (December 2016) - Valeriani, M.; Insola, A.; Mazzone, P.
Abstract : The study aimed to investigate the site of the movement related inhibition of the human dorsal column nuclei. Median nerve somatosensory evoked potentials (SEPs) were recorded from 18 patients suffering from Parkinson's disease, who underwent electrode implantation in the pedunculopontine (PPTg) nucleus. SEPs were recorded at rest and during movement of the thumb of the stimulated wrist. The PPTg electrode recorded a triphasic potential generated in the cuneate nucleus. The PPTg potential was subtended by 2 high frequency oscillation (HFO) components: (1) an earlier one with 1000 Hz frequency, and (2) a later one with 1700 Hz frequency. Movement reduced both HFO components. We suggest that the 1000 Hz and 1700 Hz HFO bursts are generated at pre- and post-synaptical level, respectively. Therefore, movement exerts both pre- and post-synaptic inhibition on the dorsal column nuclei.